2019
DOI: 10.3390/w11071386
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological Analysis of Emerging Contaminants from Wastewater Discharges in the Coastal Zone of Cihuatlán (Jalisco, Mexico)

Abstract: This research provides a baseline tool to detect, predict and scientifically evaluate the toxic environmental impact generated by chemical substances that are categorized as emerging contaminants (ECs) with endocrine disruptive action. The present study was carried out in five effluents of wastewater produced by urban and rural settlements of the coastal zone of Cihuatlan, Jalisco. Five compounds, considered ECs and that act as endocrine disruptors, were analyzed: Diclofenac, Ibuprofen, Ketorolac, Pentachlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Tables 4 and 5 present the average values of the bioconcetration (BCF) and bioaccumulative potential risk (BPR) for the NSAIDs, calculated using Equations (1)-(5) and classified using the Hakanson index. Values were calculated using the tissue sample analysis results, with the average values of NSAID concentrations in effluents reported in 2019 in [21] and the parameters in Table 2. The results of the analysis performed on the muscle tissue of the fishes demonstrated the presence of the pharmaceuticals diclofenac, ibuprofen, ketorolac and naproxen in all the species analyzed at both study sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tables 4 and 5 present the average values of the bioconcetration (BCF) and bioaccumulative potential risk (BPR) for the NSAIDs, calculated using Equations (1)-(5) and classified using the Hakanson index. Values were calculated using the tissue sample analysis results, with the average values of NSAID concentrations in effluents reported in 2019 in [21] and the parameters in Table 2. The results of the analysis performed on the muscle tissue of the fishes demonstrated the presence of the pharmaceuticals diclofenac, ibuprofen, ketorolac and naproxen in all the species analyzed at both study sites.…”
Section: Resultsmentioning
confidence: 99%
“…Tables 4 and 5 present the average values of the bioconcetration (BCF) and bioaccumulative potential risk (BPR) for the NSAIDs, calculated using Equations (1)- (5) and classified using the Hakanson index. Values were calculated using the tissue sample analysis results, with the average values of NSAID concentrations in effluents reported in 2019 in [21] and the parameters in Table 2. Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They included diclofenac, naproxen, ketorolac, and ibuprofen. Moreover, these compounds were also detected in muscle tissues of 14 fish species, which could end up in bioaccumulation in the environment and organisms (Arguello-Pérez et al, 2019). In another study, the presence of ECs in water bodies was found in Coruña, Galicia (NW Spain).…”
Section: Introductionmentioning
confidence: 91%
“…It was found from an ecotoxicological analysis. These ECs can contaminate surface water and soil and later cause endocrine changes in organisms living in this ecosystem (Arguello-Pérez et al, 2019). Endocrine disruption chemicals interfere endocrine system by mimicking, disrupting, and blocking the hormone's function (Bolong et al, 2009).…”
Section: Adverse Effect Of Emerging Contaminantsmentioning
confidence: 99%